Impact of 68Ga-FAPI positron emission tomography/computed tomography on staging and tumor management in patients with gastric cancer - Shunyu Zhang; Minggang Su; Qianrui Li; Qiancheng Hu; Xijiao Liu; Xiaolong Chen; Hongfeng Gou (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose To evaluate the added value of additional 68Ga-FAPI PET/CT following CT for primary staging, detection of postoperative recurrence, and management of gastric cancer patients. Methods We retrospectively included patients with gastric cancers who underwent contrast-enhanced computed tomography (ceCT), followed by 68Ga-FAPI PET/CT within 30 days. 68Ga-FAPI PET/CT was performed for initial staging or detection of postoperative recurrence. Two nuclear medicine physicians and a radiologist independently decided on imaging-based staging. Pre-68Ga-FAPI PET/CT treatment decisions were made by a simulated tumor board and post-68Ga-FAPI PET/CT decisions were extracted from medical records. We evaluated the impact of 68Ga-FAPI PET/CT with inconsistent new findings based on the initial findings from ceCT and the resulting changes in treatment strategies. Results We included 112 patients, 84 for initial staging and 28 for detection of postoperative recurrence. Compared to CT, 29 new findings in 24 patients were diagnosed as, or ruled out, cancer involvement on 68Ga-FAPI PET/CT. Among the 112 patients, 21 patients (18.8%) experienced changes in stage or postoperative recurrence. Among patients for initial staging, 14 had stage changes, with 10 being upstaged and 4 being downstaged. Among patients for detection of postoperative recurrence, 7 more patients were diagnosed with tumor recurrence. New findings of 68Ga-FAPI PET/CT led to treatment change in 20/112 (17.9%) patients, which was deemed of major change in 19 patients and minor change in 1 patient. Conclusions 68Ga-FAPI PET/CT is valuable for precise staging and detection of postoperative recurrence of gastric cancers, and has the potential to influence management.